Structural and Magnetic Properties of Nickel Spinel Doping Gadolinium Synthesized by using Citrate Precursor Technique - Luong, Ngoc Anh; To, Thanh Loan (Old Journal, 2017)
NiGd₀.₁Fe₁.₉O₄ nanoparticles have been synthesized by citrate precursor technique and annealed at 700° C in 5 h. Indexed X-ray diffraction (XRD) patterns analysed by Rietveld method, scanning electron microscopy (SEM) and integrals magnetometer (IM) are utilized in order to study the effect of gadolinium substitutions and its impact on crystalline size, lattice parameter, cation distribution, microstructure and magnetic properties of the NiFe₂O₄ and NiGd₀.₁Fe₁.₉O₄ samples. Results have shown that the formation of pure cubic spinel phase, the lattice parameter a increases and crystallite size D decreases with on Gd³⁺ substitution. SEM images show that the particle samples have spherical morphology and uniform size distribution. Magnetization as a function of temperature was determined via magnetization curves measured by integrals magnetometer in temperature range from 88 K to above Curie temperature in applied fields up to 10 kOe. The spontaneous magnetization Msp and Curie temperature of the samples were determined and discussed based on the influences of the particles size, cation distribution and gadolinium substitution effects.